Efficacy and safety evaluation of adalimumab for psoriatic arthritis - Zhiyue Cai; Le Yan; Yue Zhang (Medicine, 2026)
Background: This study aims to conduct a systematic evaluation of the efficacy and safety of adalimumab (ADA) in treating psoriatic arthritis (PsA), providing evidence-based reference data for clinical medicine. Methods: A systematic search was conducted in PubMed, Embase, Web of Science, the Cochrane Library, as well as Chinese databases, including China National Knowledge Infrastructure, WanFang Data, and VIP Chinese Scientific Journals Database, to identify relevant randomized controlled trials of ADA for PsA. The final search was updated on June 10, 2026. Data were analyzed using Stata 15.0. Results: This meta-analysis involved 17 studies, including 1 phase II clinical trial and 11 phase III clinical trials, covering 5655 patients. According to the meta-analysis, ADA demonstrated significant improvements in ACR20 (risk ratio [RR]: 2.27, 95% confidence interval [CI]: 1.83–2.83), ACR50 (RR: 3.92, 95% CI: 2.98–5.15), and ACR70 (RR: 5.75, 95% CI: 4.47–7.39) among PsA patients compared with the control group. In addition, it also improved PASI75 (RR: 7.07, 95% CI: 4.36–11.46), PASI90 (RR: 4.27, 95% CI: 1.64–11.14), and PASI100 (RR: 8.23, 95% CI: 3.89–17.40). Furthermore, ADA was associated with improvements in other relevant indicators, including PsA response criteria (RR: 2.45, 95% CI: 2.01–2.99), complete resolution of enthesitis (RR: 1.46, 95% CI: 1.22–1.74), and minimal disease activity (RR: 3.10, 95% CI: 2.58–3.73). The study also performed subgroup analyses for outcomes at different stages and dosing intervals. The results showed that there was no significant increase in the overall risk of adverse events (AEs; RR = 1.04) or serious AEs (RR = 1.13), and there was no notable increase in discontinuations due to AEs (RR = 1.46). In the context of specific AEs, ADA was associated with 11 types of AEs but showed almost no impact on the other 6 AEs. Conclusion: ADA demonstrated beneficial efficacy in treating PsA, as evidenced by improvements in relevant indicators. Meanwhile, ADA demonstrated overall clinical efficacy; however, it was associated with a significantly increased risk of elevated liver enzymes (alanine aminotransferase and aspartate aminotransferase), suggesting a potential signal of hepatotoxicity. While no increase in overall or serious AEs was observed, liver function monitoring may be warranted during treatment.